Tinjauan Literatur Sistematik Tentang Implementasi ISO 9001:2015: Strategi, Tantangan, dan Implikasi Terhadap Produktivitas dan Mutu Organisasi - Ramadhani Ramadhani; Rudi Khobiron; Ananda Syaiba Suri Kholafi; Mu’alimin Mu’alimin (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of ISO 9001:2015 as a quality management system standard has become a strategic issue in improving the competitiveness, efficiency, and consistency of organizational quality in the era of globalization and digitalization. However, the effectiveness of its implementation still varies depending on the organizational context, resource readiness, and quality culture. This study aims to systematically review the literature related to the implementation of ISO 9001:2015 to answer the main questions: how it affects organizational performance, how it is integrated with other management systems, and what the challenges and directions for future research are. The method used is a systematic literature review through a search of the Google Scholar and Publish or Perish databases using the keywords